The Effectiveness of The Patrol of the Pekalongan Samapta Police Unit in Order to Achieve the Maintenance of Security and Public Order - Abraham Ben Gurion (Advances in Police Science Research Journal, 2022)
The research conducted to get an overview regarding the implementation of patrols by the Unit of Turjawali on Uniform Police Unit Polres Pekalongan in an effort to be effective. This is considered important because in factual conditions the maintenance of security and public order is indicated to have not been maximized because the number of crimes, especially burglary that tends to increase every year. The implementation of patrols is expected to be a form of prevention in preventing the intention and opportunity of the criminal act of burglary in order to create security and public order. In writing this final project, the author uses management theory, effectiveness theory and competency theory as a means of author to analyze and process data obtained when conducting research, as well as several concepts and understandings to clarify understanding related to this writing. Methods of field research and data triangulation as a means of data validation. The efforts to make routine police patrols from Uniform Police Unit Polres Pekalongan effective have also not gone well because they have not been able to reach the indicators of the effectiveness of an activity, which are program understanding, goal achievement, and change-over to be better. From this research, it can be concluded that the implementation and effectiveness of Uniform Police Unit in police patrols to realizing public security is still not maximized based on the theory and analytical methods used by author and also the influencing factors, especially in the internal sphere in the form of human resources and methods used in the planning, implementation, and supervision and control. Therefore, there is a need for coordination and improvement of each stage of routine patrols for an effective implementation itself.